Malignant mediastinal mesothelioma treated with anlotinib: a case report and review of the literature - Zhang, Yishi; He, Wan; Zhan, Ke; Zhang, Luobin; Cao, Hua; Xu, Ruilian (Frontiers in Oncology, 2023)
Malignant mesothelioma that originates from mediastinal (MMM) is a rare form of malignant pleural mesothelioma (MPM). The prognosis of advanced stage MPM was poor, and the traditional treatment was chemotherapy. Here, we present a patient with MMM that was treated with anlotinib, a multitargeted tyrosine kinase inhibitor (TKI) who had a 24-month progression-free survival (PFS). Further review of the literature showed that, despite some explorations of applying small-molecule multitargeted TKIs in the treatment of MPM, until today, no large series had a positive result. Anlotinib had been approved by the China Food and Drug Administration on treating non–small cell lung cancer, soft tissue sarcoma, renal cell carcinoma, and medullary thyroid cancer. We assumed that the ability of anlotinib to target more tyrosine kinase receptors than most of other TKIs could contribute to the long duration of PFS in this case, but further study is needed to further validate the efficacy of anlotinib in treatment of MPM.